Organizational communication and the environment: environmental management through communication in companies (Research, Society and Development, 2020)
The human being has dedicated decades of his reflections on business management, thinking about ways to grow his enterprise and multiply his profit exponentially. Abandoning the idea of indiscriminate growth for good, he entered the era of sustainable development and, along with the idea of sustainability, came the need to improve his own sense of management. Despite the need to understand this paradigmatic reformulation of principles and precepts, it was essential to introduce and improve organizational communication, which often did not follow the ecological idea arising from this new sustainable format. Through a qualitative and descriptive research, bibliographic analysis was chosen so that, referenced in articles with high indexation, we seek to point out the characteristics of environmental management in a conceptual and comparative perspective. Through the research carried out, it was possible to verify that communication, as it is inserted in the organizational context today, has obtained several approaches and provided an effective adaptation of organizations in the midst of social and technological changes, enabling a renewed corporate image, more open to the access of its public, more resilient and, certainly, much more dynamic.